The Politics of International Terrorism in the Security Complexes in the Greater Horn of Africa: An Overview from Uganda under the Movementocracy - Mukwaya, Aaron K.K. (African Journal of International Affairs, 2004)
The article attempts to analyse the phenomenon of international terrorism in the Greater Horn Security Complexes, with the emphasis on the role of Uganda’s Movementocratic government. The article is premised on the thesis that ‘International Terrorism’, apart from its local, national, regional and global causes, has become one of the key determinants of foreign policy and regional relations in the Greater Horn of Africa, and even more so for Uganda. It asserts that given the uniqueness of the Movementocracy and the global appraisal of this governance, Uganda is at the moment standing up to be counted by western countries as one of the vanguards in the fight against international terrorism in the Greater Horn of Africa. It also considers the causes and consequences of international terrorism and the methodologies and strategies for addressing this political scourge at the local, national, regional, continental and global levels. Here we shall examine unilateral, bilateral and multilateral approaches in dealing with international terrorism through states and non-states arrangements and methodologies.